2016
DOI: 10.1002/anie.201606415
|View full text |Cite
|
Sign up to set email alerts
|

Sodium and Manganese Stoichiometry of P2‐Type Na2/3MnO2

Abstract: To realize a reversible solid-state Mn(III/IV) redox couple in layered oxides, co-operative Jahn-Teller distortion (CJTD) of six-coordinate Mn(III) (t2g (3) -eg (1) ) is a key factor in terms of structural and physical properties. We develop a single-phase synthesis route for two polymorphs, namely distorted and undistorted P2-type Na2/3 MnO2 having different Mn stoichiometry, and investigate how the structural and stoichiometric difference influences electrochemical reaction. The distorted Na2/3 MnO2 delivers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
248
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 234 publications
(272 citation statements)
references
References 22 publications
15
248
0
Order By: Relevance
“…In the continuous charge process, anion redox could occur according to the similar phenomenon in other P2 analogues32–34 and a total amount of 0.56 Na + are expected to be extracted (corresponding to Na 0.07 ZnMnO 2 ). On the other hand, the charge plateau observed at high potential is a fingerprint of anion redox reaction30–34 that contributes to most of the detected capacity 27,29–34. In the first discharge process, a discharge capacity of 202.4 mAh g −1 can be achieved, corresponding to 0.79 Na + insertion into the NZM host leading to a formula of Na 0.86 MnO 2 .…”
Section: Resultsmentioning
confidence: 85%
“…In the continuous charge process, anion redox could occur according to the similar phenomenon in other P2 analogues32–34 and a total amount of 0.56 Na + are expected to be extracted (corresponding to Na 0.07 ZnMnO 2 ). On the other hand, the charge plateau observed at high potential is a fingerprint of anion redox reaction30–34 that contributes to most of the detected capacity 27,29–34. In the first discharge process, a discharge capacity of 202.4 mAh g −1 can be achieved, corresponding to 0.79 Na + insertion into the NZM host leading to a formula of Na 0.86 MnO 2 .…”
Section: Resultsmentioning
confidence: 85%
“…Owing to the redox activity of both Mn and O, Na 2 Mn 3 O 7 delivers a large reversible capacity of ≈200 mAh g −1 with the capacity retention of 85% after 20 cycles (Figure 6b). [35] [35] …”
Section: Resultsmentioning
confidence: 99%
“…The electrochemical mechanisms of distorted and undistorted P2‐type Na 2/3 MnO 2 were studied by Komaba's group. It was found that the distorted (P′2‐type) Na 2/3 MnO 2 delivered a high capacity of 216 mAh g −1 as a 3 V class cathode material, with excellent cycling stability and better electrochemical behavior compared to the undistorted Na 2/3 MnO 2 , as presented in Figure a,b . Monoclinic α‐NaMnO 2 (C2/m) shows an initial capacity of 185 mAh g −1 when cycling between 3.8 and 2.0 V. It also experiences fast capacity decay, however, in subsequent cycles …”
Section: Transition Metal Oxide Cathodes For Sodium Ion Storagementioning
confidence: 94%
“…Charge–discharge profiles of different single metal oxide cathodes for SIBs: a) P2‐Na 2/3 MnO 2 and b) P′2‐Na 2/3 MnO 2 . Reproduced with permission . Copyright 2016, Wiley‐VCH.…”
Section: Transition Metal Oxide Cathodes For Sodium Ion Storagementioning
confidence: 99%